Edukasi Penyalahgunaan Obat Resep terhadap Kesehatan Jiwa Remaja di Sekolah Menengah Pertama Negeri 2 Kecamatan Galesong Utara Kabupaten Takalar - Fitriani, Nurlaila; Astuti, Ayun Dwi; Fadilah, Nur; Febrianty, Eva; Azzahra, Nur Inaayah; Nurazizah, Nurazizah; Rasak, Risna (Jurnal Abdimas Kesehatan (JAK), 2025)
Prescription drug abuse has been widely practiced by adolescents in Indonesia. Seeing this condition requires an intervention that can increase adolescent knowledge related to prescription drug abuse. Psychoeducation for students of SMPN 2 North Galesong is one of the interventions to educate students, teachers, and parties related to the impact of prescription abuse among adolescents. The results of the implementation of this community service obtained that students' knowledge related to prescription drug abuse predominantly increased as evidenced by the highest score in the pre-test of only 60 to 100 in the post-test. In conclusion, there was an increase in knowledge in students of SMPN 2 North Galesong after being given psychoeducation related to prescription drug abuse. The Hasanuddin University community service team hopes that this psychoeducation can prevent prescription drug abuse in adolescents